Sex Role Reversal and High Frequency of Social Polyandry in the Pheasant-Tailed Jacana (Hydrophasianus chirurgus) - Fresneau, Nolwenn; Lee, Ya-Fu; Lee, Wen-Chen; Kosztolányi, András; Székely, Tamás; Liker, András (Frontiers in Ecology and Evolution, 2021)
In a few species, males invest more than females in parental care while the females invest in mating competition and producing multiple broods for several mates. Species in the family Jacanidae are commonly used for studying this type of breeding system (called sex-role reversal), and previous studies found discrepancies and variation between species in the expected characteristics of reversed sex roles. Yet, a better understanding of sex role differences in breeding behaviour in such species is crucial for disentangling possible evolutionary mechanisms leading to this peculiar breeding system. Sex-role reversal in the pheasant-tailed jacana Hydrophasianus chirurgus has been documented long time ago. Since the very early observation of this species, there was no attempt to provide a comprehensive and quantitative description of their breeding. This study aims to fill these knowledge gaps by investigating the sex role differences in the breeding behaviour of pheasant-tailed jacanas, by observing and monitoring a breeding population in Taiwan. We focused on three main characteristics of sex-role reversal: (1) competition between females for access to males, such as agonistic and courtship behaviours, (2) polyandrous mating, and (3) male-only care. As expected, we found that females provide most of the territory defence toward conspecifics. Males also participated in agonistic behaviours, although less frequently than females. Furthermore, contrary to what was expected, we found that males spent more time than females on courtship behaviour. Polyandrous females performed mating and laying sequentially with different mates but maintained the pair bonds simultaneously with multiple males. For the first time for the species, we could estimate that the average number of mates per female (i.e. degree of polyandry) was 2.4 and that at least 81.8% of the females in the population were polyandrous. Finally, our observations corroborated that brood care is predominantly provided by males, nevertheless females were also participating to some degree in brood attendance but never in direct care. This study highlights that some aspects of polyandrous breeding might deviate from stereotyped view on sex-role reversal, and stress the importance of further within species and comparative studies in order to fully understand the mechanisms leading to sex-role reversal.